Bubble Column Hydrodynamic Study with Experimental Investigation and CFD Computations - Habobi, Naseer; Majeed, Reeham; Kuba, Ali Essam (Nahrain University College of Engineering Journal, 2008)
By achieving simulation of hydrodynamics in a bubble column reactor, have taken an important step towards designing an efficient slurry reactor for large-scale conversion of synthesis gas to liquid hydrocarbons. The simulation allows determining gas holdup, a key variable affecting the reaction rate of gas-to-liquid (GTL) conversion using Fischer- Tropsch (FT) chemistry. This work have two parts, the first part experimental work with bubble column with specific conditions and the second deals with computational fluid dynamics CFD for bubble column have the same geometry and operating conditions. This study is to clarify experimentally the effect of superficial gas velocity on the gas holdup, and the mass transfer coefficient (kLa) where each of them increases as the superficial gas velocity increase. NaCl addition will increase the transition velocity and the gas holdup for certain concentration and superficial gas velocity 2-D simulation was applied in this work. Gas holdup computational results using ANSYS CFX used on Eulerian-Eulerian multiphase model have been compared to experimental data. These results for airwater system were encouraging against the experiment result